2020
DOI: 10.1001/jamadermatol.2020.1852
|View full text |Cite
|
Sign up to set email alerts
|

Administrative Burden and Costs of Prior Authorizations in a Dermatology Department

Abstract: nsurance companies use prior authorizations (PAs) to address inappropriate prescribing and unnecessary variations in care, commonly for expensive medications and procedures. However, PAs often delay and sometimes prevent essential and appropriate treatments and are associated with poor patient outcomes. 1,2 Prior authorizations add administrative burden to physician offices and appear to be increasing over time. [1][2][3][4][5] The American Medical Association has called for PA reform. 3 Dermatology has been d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(24 citation statements)
references
References 13 publications
1
17
0
Order By: Relevance
“…To provide context, assuming an annual expenditure of $1.7 billion USD for radiation oncology services at academic/university practices in 2018 (Appendix Given this and other multispecialty data highlighting the burden of PA, determining the net savings to the health care system as a result of PA is critical. [10][11][12][13][14] For example, in an analysis of superficial venous procedures at an academic medical center, PA was estimated to save less than $60,000 USD annually while increasing administrative expenses by more than $110,000 USD. 13 Although an imperfect representation of savings, PA denial rates may provide some indication of PA effectiveness in radiation oncology.…”
Section: Discussionmentioning
confidence: 99%
“…To provide context, assuming an annual expenditure of $1.7 billion USD for radiation oncology services at academic/university practices in 2018 (Appendix Given this and other multispecialty data highlighting the burden of PA, determining the net savings to the health care system as a result of PA is critical. [10][11][12][13][14] For example, in an analysis of superficial venous procedures at an academic medical center, PA was estimated to save less than $60,000 USD annually while increasing administrative expenses by more than $110,000 USD. 13 Although an imperfect representation of savings, PA denial rates may provide some indication of PA effectiveness in radiation oncology.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have found that physicians spend substantial time and resources fulfilling UM requirements. 4,6 Studies have also found that, while UM tools such as prior authorization and step therapy protocols typically reduce drug utilization, in some cases they can adversely impact patient adherence to care and clinical outcomes. 7 However, health plans' use of prescriber requirements in their drug coverage policies is not well understood.…”
Section: What This Study Addsmentioning
confidence: 99%
“…[8] Poor coding practices complicate the surgical workflow, create delays or cancelations, and reduce the quality of patient care delivered. [9] To ensure proper reimbursement, the scheduled or preauthorized CPT code must match the performed procedure. A mismatch between codes can increase the likelihood of insurance denials that result in lower or no reimbursement.…”
Section: Introductionmentioning
confidence: 99%